HIGH DOSES OF STATINS BEFORE PERCUTANEOUS CORONARY INTERVENTION: WHETHER THERE ARE REASONS TO USE? - I. S. Yavelov; M. V. Zhatkina; O. M. Drapkina; A. Yu. Gorshkov; N. O. Myasnikova (Столичная издательская компания, 2017)
The results of prospective randomized clinical trials planned to assess the efficacy of using statins in high doses before percutaneous coronary interventions (PCI) are presented in the review. The effect of this approach on the severity of myocardial damage and clinical outcomes in planned PCI in patients with stable ischemic heart disease (IHD) and early PCI in acute coronary syndrome (ACS) without stable ST-segment elevation was found. The results of the trials planned to study the incidence of contrast-induced nephropathy as well as data from meta-analyzes of conducted clinical trials are demonstrated.According to the accumulated facts, taking high doses of statins before PCI can contribute to reduce myocardial damage with a decrease in the risk of periprocedural myocardial infarction. This effect was demonstrated in the planned coronary stenting in patients with stable IHD and in PCI in the first days of treatment of ACS without the stable ST-segment elevation. It was found both in patients who had not previously taken statins and in patients permanently treated with statins. The additional expected benefit of using a high dose of statins prior to PCI is the prevention of contrast-induced nephropathy. However, due to the limited evidence base, there is no consensus on the advisability of such an approach in current clinical guidelines.